Analisis Pengaruh Tingkat Literasi Digital terhadap Produktivitas Kerja Pada Dosen Dalam Menghadapi Pendidikan Era Society 5.0 di Kota Medan - Adriansyah, T.M.; Rahmayati, T.Elfira (CV. Utility Project Solution, 2023)
This research aims to see the influence of digital literacy levels on lecturers' work productivity in facing education in the era of society 5.0. in the city of Medan. This study uses a quantitative approach method. This research refers to the framework in the 2020-2024 Digital Literacy Road Map which is measured by four pillars which are part of the digital literacy curriculum development framework, namely digital skills, digital ethics, digital security and digital culture, which consists of 30 indicators. Meanwhile, lecturers' work productivity is measured based on work productivity measurements including work quantity, work quality and timeliness based on Simamora's theory. The sampling technique in this study used incidental sampling with 100 lecturers in the city of Medan as respondents. Research was analyzed quantitatively with linear regression analysis method. The results of this research show a significant value of 0.000 (p<0.005), so it can be concluded that there is a positive and significant influence of digital literacy levels on lecturers' work productivity in facing education in the era of society 5.0. that is equal to 70% while 30% contributed by other variables.